A multicellular liver organoid model for investigating hepatitis C virus infection and nonalcoholic fatty liver disease progression - Lee, Jaeseo; Gil, Dayeon; Park, Hyeyeon; Lee, Youngsun; Mun, Seon Ju; Shin, Yongbo; Jo, Eunji; Windisch, Marc P.; Kim, Jung Hyun; Son, Myung Jin (Hepatology, 2024)
Background and Aims: HCV infection can be successfully managed with antiviral therapies; however, progression to chronic liver disease states, including NAFLD, is common. There is currently no reliable in vitro model for investigating host-viral interactions underlying the link between HCV and NAFLD; although liver organoids (LOs) show promise, they currently lack nonparenchymal cells, which are key to modeling disease progression. Approach and Results: Here, we present a novel, multicellular LO model using a coculture system of macrophages and LOs differentiated from the same human pluripotent stem cells (PSCs). The cocultured macrophages shifted toward a Kupffer-like cell type, the liver-resident macrophages present in vivo, providing a suitable model for investigating NAFLD pathogenesis. With this multicellular Kupffer-like cell-containing LO model, we found that HCV infection led to lipid accumulation in LOs by upregulating host lipogenesis, which was more marked with macrophage coculture. Reciprocally, long-term treatment of LOs with fatty acids upregulated HCV amplification and promoted inflammation and fibrosis. Notably, in our Kupffer-like cell-containing LO model, the effects of 3 drugs for NASH that have reached phase 3 clinical trials exhibited consistent results with the clinical outcomes. Conclusions: Taken together, we introduced a multicellular LO model consisting of hepatocytes, Kupffer-like cells, and HSCs, which recapitulated host-virus intercommunication and intercellular interactions. With this novel model, we present a physiologically relevant system for the investigation of NAFLD progression in patients with HCV.
Keywords: Coculture Techniques; Disease Progression; Hepacivirus; Hepatitis C; Humans; Kupffer Cells; Liver; Macrophages; Models, Biological; Non-alcoholic Fatty Liver Disease; Organoids